2015
DOI: 10.3171/2015.6.focus15219
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic thoracic outlet syndrome: current diagnostic criteria and advances in MRI diagnostics

Abstract: Neurogenic thoracic outlet syndrome (nTOS) is caused by compression of the brachial plexus as it traverses from the thoracic outlet to the axilla. Diagnosing nTOS can be difficult because of overlap with other complex pain and entrapment syndromes. An nTOS diagnosis is made based on patient history, physical exam, electrodiagnostic studies, and, more recently, interpretation of MR neurograms with tractography. Advances in high-resolution MRI and tractography can confirm an nTOS diagnosis and identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 24 publications
0
28
0
3
Order By: Relevance
“…This technique uses heavy T2 weighting, fat suppression, and pulsation artifact suppression to image peripheral nerves while simultaneously suppressing the surrounding tissue. Common MRN sequences include standard spin‐echo T1‐weighted images and fast spin‐echo T2‐weighted images with fat suppression, as well as short‐tau inversion recovery sequences (to provide intrinsic fat suppression) and a newer protocol, termed SPAIR (T2 spectral adiabatic inversion recovery), which enhances the signal‐to‐noise ratio and further suppresses fatty tissue . This technique, which generates nerve images referred to as neurograms, can demonstrate nerve fiber deviations, such as those resulting from fibrous bands.…”
Section: True Neurogenic Tosmentioning
confidence: 99%
“…This technique uses heavy T2 weighting, fat suppression, and pulsation artifact suppression to image peripheral nerves while simultaneously suppressing the surrounding tissue. Common MRN sequences include standard spin‐echo T1‐weighted images and fast spin‐echo T2‐weighted images with fat suppression, as well as short‐tau inversion recovery sequences (to provide intrinsic fat suppression) and a newer protocol, termed SPAIR (T2 spectral adiabatic inversion recovery), which enhances the signal‐to‐noise ratio and further suppresses fatty tissue . This technique, which generates nerve images referred to as neurograms, can demonstrate nerve fiber deviations, such as those resulting from fibrous bands.…”
Section: True Neurogenic Tosmentioning
confidence: 99%
“…Specifically, variations of MRN such as Short Tau Inversion Recovery (STIR) sequences and the Spectral Adiabatic Inversion Recovery (SPAIR) preparatory module deliver a more complete anatomical description of the nerves comprising the brachial plexus. Additionally, the use of diffusion tensor imaging sequences to visualize nerve fascicles is employed in the modeling technique of tractography, which allows for a more comprehensive assessment of peripheral nerve injury [9]. One study using MRN demonstrated a 100% positive predictive value in all thirty patients.…”
Section: Diagnostic Techniquesmentioning
confidence: 99%
“…The addition of diffusion tensor imaging (DTI) to standard MRN sequences may even permit visualization of individual nerve fascicles. Such techniques may permit direct imaging of nerve compression or impingement by bony, muscular, or fibrous structures [30]. In classic nTOS, MRN may be able to directly visualize anomalies of the lower brachial plexus cords, such as compression, flattening, or neural and peri-neural inflammation.…”
Section: The Role Of Imaging In Diagnosis Of Ntosmentioning
confidence: 99%